Global, regional, and national trends of measles burden and its vaccination coverage among children under 5 years old: An updated systematic analysis from the Global Burden of Disease Study 2021 - Weiyang Chen; Min Du; Jie Deng; Min Liu; Jue Liu (International Journal of Infectious Diseases)
Objectives: This study examines trends in measles burden and measles-containing vaccine (MCV) coverage among children under 5 years old, with a focus on the impact of the COVID-19 pandemic. Methods: We analyzed measles incidence, mortality, and disability-adjusted life years (DALYs) in children under 5 years old using Global Burden of Disease 2021 data and MCV coverage in 204 countries from the Global Health Data Exchange. Trends from 1990 to 2021 were assessed through estimated annual percentage change (EAPC) at global, regional, and national levels. Results: In 2021, measles caused 4.1 million cases, 48.1 thousand deaths, and 4.2 million DALYs among children under 5 years old globally. From 1990 to 2021, incidence, mortality, and DALYs declined by over 90%, but low socio-demographic index regions continued to bear the highest burden. During the COVID-19 pandemic (2019-2021), the global measles burden declined overall, but mortality (EAPC = 155.55, 95% confidence interval [CI]: 53.89-324.38) and DALY rates (EAPC = 146.94, 95% CI: 46.25-316.94) in East Asia increased. The pandemic also disrupted vaccination, with MCV1 coverage declining (EAPC = −2.08, 95% CI: −3.30 to −0.85), reversing previous trends in 68 countries (33.33%) for MCV1 and 50 countries (24.51%) for MCV2. Conclusion: Global measles incidence has declined over the past 30 years, but regional disparities persist. The COVID-19 pandemic disrupted vaccination efforts, raising the risk of outbreaks among children. Enhanced efforts are critical to achieving measles elimination.